Using Caenorhabditis elegans to Model Therapeutic Interventions of Neurodegenerative Diseases Targeting Microbe-Host Interactions - Wang, Chenyin; Zheng, Chaogu (Frontiers in Pharmacology, 2022)
Emerging evidence from both clinical studies and animal models indicates the importance of the interaction between the gut microbiome and the brain in the pathogenesis of neurodegenerative diseases (NDs). Although how microbes modulate neurodegeneration is still mostly unclear, recent studies have started to probe into the mechanisms for the communication between microbes and hosts in NDs. In this review, we highlight the advantages of using C. elegans to disentangle the microbe-host interaction that regulates neurodegeneration. We summarize the microbial pro- and anti-neurodegenerative factors identified using the C. elegans ND models and the effects of many are confirmed in mouse models. Specifically, we focused on the role of bacterial amyloid proteins, such as curli, in promoting proteotoxicity and neurodegeneration by cross-seeding the aggregation of endogenous ND-related proteins, such as alpha-synuclein. Targeting bacterial amyloid production may serve as a novel therapeutic strategy for treating NDs, and several compounds, such as EGCG, were shown to suppress neurodegeneration at least partly by inhibiting curli production. Because bacterial amyloid fibrils contribute to biofilm formation, inhibition of amyloid production often leads to the disruption of biofilms. Interestingly, from a list of 59 compounds that showed neuroprotective effects in C. elegans and mouse ND models, we found that about half of them are known to inhibit bacterial growth or biofilm formation, suggesting a strong correlation between the neuroprotective and antibiofilm activities. Whether these potential therapeutics indeed protect neurons from proteotoxicity by inhibiting the cross-seeding between bacterial and human amyloid proteins awaits further investigations. Finally, we propose to screen the long list of antibiofilm agents, both FDA-approved drugs and novel compounds, for their neuroprotective effects and develop new pharmaceuticals that target the gut microbiome for the treatment of NDs. For this end, the C. elegans ND models can serve as a platform for fast, high-throughput, and low-cost drug screens that target the microbe-host interaction in NDs.